PERMOHONAN SURAT IZIN PRAKTIK BIDAN (SIPB) BERDASARKAN PERATURAN MENTERI KESEHATAN NO. 1464/MENKES/PER/X/2010 TENTANG IZIN DAN PENYELENGGARAAN PRAKTIK BIDAN DI KABUPATEN BREBES - Diana Novy Fikria (Jurnal Idea Hukum, 2016)
Midwives as one ofthe health workers in the organized practice of compulsory kebidanannya has permission from the Government in the form of License the practice of Midwives. One of midwives ties Indonesia. Recommendation IBI in Brebes Regency can be obtained if the Member already has a certificate of Contraception technology updates. CTU is not aligned with the the conditions to get the SIPB i.e. the recommendations of professional organizations of authority contained in the regulation of midwives, the Minister of health no. 1464/Menkes/Per/X/2010 about permitsand Conducting the practice of Midwives.This research aims to analyze the petition Passes the practice of midwives and to analyze the constraints that hinder the application based Regulations SIPB Minister of health no. 1464/Menkes/Per/X/2010 about permits and Conducting the practice of Midwives. This research is qualitative research with the juridical sociological approach.The results show that the petition SIPB in Brebes Regency have not fully in accordance with Permenkes No. 1464/Menkes/Per/X/2010 about permits and Conducting the practice of Midwives. Resistance to get recommendations from IBI members must attend training CTU,compliance requirement application in collecting Member SIPB vary resulting in a filing process lasts a long time as well as the policies of the health service and IBI Brebes Regency that enforces two Ante Natal Care SIPB authority and Post Natal Care and the SIPB ANC, INC. and Intra Natal Care.Â Keyword: health, permited, midwive